2007
DOI: 10.1088/0029-5515/47/8/026
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence suppression in the neighbourhood of a minimum-qsurface due to zonal flow modification in reversed shear tokamaks

Abstract: Zonal flow behaviour and its effect on turbulent transport in tokamak plasmas with reversed magnetic shear are investigated by global fluid simulations of electrostatic ion temperature gradient driven turbulence. It is found that for high q (safety factor) turbulent transport is high even at a minimum-q region because oscillatory zonal flows called geodesic acoustic modes (GAMs) are dominant. The turbulent transport is reduced in the neighbourhood of a minimum-q surface when q is low enough to damp the GAMs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…It is interesting to note that in simulations, damping of the GAM due to coupling to higher m modes has been found [27,28,29]. It is evident that using the wave kinetic equation such damping would inevitably be found by allowing the energy to be distributed among several modes.…”
Section: Introductionmentioning
confidence: 96%
“…It is interesting to note that in simulations, damping of the GAM due to coupling to higher m modes has been found [27,28,29]. It is evident that using the wave kinetic equation such damping would inevitably be found by allowing the energy to be distributed among several modes.…”
Section: Introductionmentioning
confidence: 96%
“…A popular theory is that the zero magnetic shear at the radial location of the q min weakens the coupling of the poloidal harmonics, which creates a gap in the toroidal eigenmodes of the ion temperature gradient ͑ITG͒ instability 5 around the q min region due to the rarefaction of the mode rational surfaces 6 or the presence of a flow shear. 7 Beyond the linear theory, a gap in the fluctuation intensity could also be created by enhanced generation of sheared flows 6,8 and convective cells, 9 or the fluctuationinduced profile corrugations. 10 However, some nonlinear simulations do not observe such a mode gap due to the existence of a slablike branch of the ITG instability 11 or the turbulence spreading and avalanche.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that in simulations, damping of the GAM due to coupling to higher m modes has been found. [31,32,33] In a careful evaluation of the contributions from higher m modes it can be shown that they are, in general, of the order ǫ n smaller. However, the effect of higher harmonics is increased by the square of the safety factor (q) and thus in order to evaluate the effects a more detailed study is called for.…”
Section: Introductionmentioning
confidence: 99%